Transmission Electron Microscopy Characterization of High-Temperatur Oxidation of Fe-20Cr-5Al Alloy Prepared by Focused Ion Beam Technique - Dani, Mohammad; Untoro, Pudji; Putra, Teguh Yulius Surya Panca; Parikin, Parikin; Mayer, Joachim; Dimyati, Arbi (UI Scholars Hub, 2015)
The Focused Ion Beam (FIB) technique was applied for cross section preparation of the oxidized alloy for Transmission Electron Microscopy (TEM) study. Prior to preparation, the specimens of Fe-20Cr-5Al alloy sheet were oxidized in air at 1200 oC for 2 minutes, 10 minutes, 2 hours, and 100 hours. The microstructure and elemental composition of the samples were characterized using TEM equipped with an Energy Dispersive X-Ray Spectroscopy (EDX). The Electron Energy Loss Spectroscopy (EELS) was used to determine of the light elements. The TEM investigation reveals remarkable microstructure evolution of the specimens during oxidation which generally exhibit a typical multi-layer structure. The TEM images, however, can provide detailed description about the phases occur after oxidation such as the Tungsten (W) and the Gallium (Ga) layers on top of the samples obviously formed during FIB preparation, the formation of Al2O3 and Cr2O3 layer, MgAl2O4 spinel, porosity, Zr/Hf/Mg phases or clusters inside the oxide scale. Hence, the FIB technique has been proven to be reliable preparation technique for microstructural and elemental studies of Fe-20Cr-5Al alloy using TEM.